PENGARUH NET PROFIT MARGIN DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERBANKAN PADA BURSA EFEK INDONESIA PERIODE TAHUN 2009 – 2012 - Shinta Asih (Computer Based Information System Journal, 2013)
The movement of stock prices are influenced by many things or factors, and this study aimed to determine the effect of net profit margin ( NPM ), and Return on Equity ( ROE ) of the company's stock price in the banking sector are listed in the Indonesia Stock Exchange. The data used in the form of secondary data from financial year 2009 to 2012. Population is banking sector companies listed on the Stock Exchange are taken of 9 samples. The data was collected in 2013 . All data have been collected descriptive first tested , the test is also done which includes the classic assumption test for normality, multi-collinear test , test and test heterocedasticity autocorrelation. Then hypotheses test using regression analysis, coefficient of determination, t-test to test the partial regression coefficients and F test to test the significance of the effect together with the level of significance of 5%. The results showed that the partial regression coefficients ( individual ) Net Profit Margin ( X1 ) effect on stock prices as a significant level of 0.001 < 0.05, and the regression coefficient Return on Equity ( X2 ) effect on stock prices as a significant level of 0.000 < 0.05. And together ( Simultaneous ) Net Profit Margin and Return on Equity has significant influence on the stock price of 0.000 < 0,05. While the coefficient of determination indicates that jointly Net Profit Margin ( NPM ), and Return on Equity provides a strong influence on stock price by 46.9 % and the two variables have a positive relationship while the remaining 53.1 % is influenced by other factors. Finally, the author suggests the Banking Companies listed on the Indonesia Stock Exchange so that the ratio of the banking company's performance can be explored in other financial ratios that affect the company's share price.